Disability and Vocational Rehabilitation in Rural Settings - Harley, Debra A.; Ysasi, Noel A.; Bishop, Malachy L. (Springer, 2018)
As editors of this book, Noel, Malachy, Allison, and I have over 45 years of combined experience in education, research, and service delivery in rehabilitation, disability, social justice, and social services. As faculty members in rehabilitation counseling education programs, we were looking for a book on rural rehabilitation and discovered a 1999 edition as the most current. The United States and other countries are nations of primarily rural landmass; therefore, understanding the challenges of rural residents with disabilities in these regions is important in service delivery, education and training, research, and funding and policy development. In addition to areas in which the terms rural, frontier, territory, and remote regions are identified specifically in chapters, throughout this book, the term rural is used as an umbrella term that is inclusive of all others. Our goal for this book is to discuss both challenges and strengths of rural life. We acknowledge the diversity and complexity of rural regions, but they share some common characteristics. Our 38 chapters cover the following topics pertaining to disabilities in rural communities: economic development; poverty; transportation, accessibility, and accommodation; technology; healthcare; ethical practice and dual relationships; resilience and strengths; military personnel; marginalized racial and ethnic adults and cultural competence and social justice; adolescents and transition students; offender populations; American Indians; agricultural, farm, and immigrant workers; sensory impairments; international perspectives from Africa, Asia-Pacific region, Australasia, Canada, Mexico, India, Turkey, Colombia, and the United Kingdom; multiple sclerosis; substance-related and addictive disorders; Workforce Innovation and Opportunity Act; impact of the Americans with Disabilities Act; forensic vocational rehabilitation; climate and weather; developing personnel through online learning; recruiting and retaining rehabilitation counselors in rural communities; capacity building and collaboration; volunteers and paraprofessionals; and research and evidence-based practices. Our comprehensive text recognizes the challenges faced by vocational rehabilitation, like other human service providers in rural communities, which are well documented. Our text provides a perspective to rethink the delivery of vocational rehabilitation services in rural areas. A unique feature is that authors of individual chapters represent an array of diverse backgrounds and expertise, including doctoral students in rehabilitation counseling. The inclusion of an international perspective adds to the understanding of globalization of disabilities in rural areas.
Challenges to Service Delivery